Case Report: Effective Use of the Orticochea Flap in the Surgical Treatment of Non-Hodgkin Lymphoma - Anastasia Dessy Harsono; Metaudina Chandra Pratiwi; Dominic Melino Tjokrovonco (Perkumpulan Kedokteran Militer, 2024)
Non-Hodgkin lymphoma is a malignant disease arising from lymphoid tissues, primarily affecting the lymph nodes. The clinical manifestations and histological appearances of non-Hodgkin lymphoma are diverse, typically presenting with swelling, pain, and ulcers in the head and neck region. This case report discusses the management of a 55-year-old immunocompetent female patient presenting with a large, painless mass extending from the neck to the occipital region of the scalp, mimicking the features of a sarcoma. Closing scalp defects poses a significant challenge for plastic surgeons due to the limited tissue and variable elasticity of the scalp. Orticochea flap, also known as the